The compound paraquat dichloride hydrate significantly affects the in vitro growth rate of a Chromobacterium violaceum wild type strain - Gabriel, Jane Eyre; de Souza, Denise Andréa Silva; de Carvalho, Francisco Allan Leandro; Madeira, Humberto Maciel França (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: the toxicity of pesticides on bacterial cell growth is still limited. Objectives: The current study aimed to assess the in vitro growth rate of the C. violaceum wild type strain ATCC12472 exposed to the herbicide paraquat dichloride hydrate at different incubation times and final concentrations. Methodology: bacterial inocula were incubated in a nutrient broth medium containing the compound paraquat at final concentrations 100 and 1.000 µg mL-1 under aeration conditions. Spectrophotometric readings at different incubation times were carried out to estimate the in vitro bacterial growth rate. Moreover, the number of viable bacteria cells in the samples was also estimated in the presence of the paraquat at two concentrations tested based on colony-forming units grown on the nutrient broth agar. Results: significant decreases in the C. violaceum growth rate were detected, after one hour of paraquat exposure at a final concentration of 1,000 µg mL-1 (p<0.05) compared to all treatments tested. After two hours of paraquat exposure, significant decreases were progressively found at all final concentrations of 100 (p<0.01) and of 1,000 µg mL-1 (p<0.001). These data were also corroborated by counting the total number of colony-forming units at final concentrations tested. Conclusion: the findings described in current study suggest that the compound paraquat dichloride hydrate exerts significant effects on the in vitro growth rate of a C. violaceum wild type strain.